Evaluation of the prognostic potential of EGFL7 in pilocytic astrocytomas - Brunhara, Bruno B.; Becker, Aline P.; Neder, Luciano; Gonçalves, Paola G. [UNESP]; de Oliveira, Cristiane [UNESP]; Clara, Carlos A.; Reis, Rui M.; Bidinotto, Lucas T. [UNESP] (Wiley, 2021)
Pilocytic astrocytoma (PA) is the most frequent solid neoplasm in childhood. It has a good 5-year overall survival (90% in childhood and 52% in adults). However, up to 20% of patients experience residual tumor growth, recurrence, and death. Although the main genetic alteration of PAs, including KIAA1549:BRAF fusion, involves chromosome 7q34, we previously found frequent loss in chr9q34.3 locus in a small subset of these tumors. Among the genes present in this locus, EGFL7 is related to poor prognosis in several tumor types. In this study, we aimed to assess EGFL7 expression through immunohistochemistry, and to evaluate its prognostic value in a series of 64 clinically and molecularly well-characterized pilocytic astrocytomas. We found high expression of EGFL7 in 71.9% of patients. Low EGFL7 expression was associated with older patients, the mean age mainly older than 11 years (P = 0.027). EGFL7 expression was not associated with presence of KIAA1549:BRAF fusion, BRAF mutation, FGFR1 mutation, nor FGFR1 duplication. Moreover, high EGFL7 expression was associated with high FGFR1 (P = 0.037) and 5′-deoxy-5′-methyltioadenosine phosphorylase (MTAP) (P = 0.005) expression, and with unfavorable outcome of patients (P = 0.047). Multivariate analysis revealed low EGFL7 expression related to older patients and high EGFL7 expression related to retained expression of MTAP. In addition, we found a borderline significance of unfavorable outcome and high EGFL7 expression. Finally, EGFL7 expression was not associated with overall or event-free survival of PA patients. Our findings point to EGFL7 expression as a novel candidate prognostic marker in PA, which should be further investigated.
Keywords: EGFL7; FGFR1; immunohistochemistry; MTAP; pilocytic astrocytoma